Eyes of Faith: The Sense of the Faithful and the Church's Reception of Revelation - Rush, Ormond (Catholic University of America Press, 2009)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- One . The Principle: The Holy Spirit, Faith, and Sensus Fidei -- 1. The Holy Spirit and Revelation -- 2. The Holy Spirit and the Church -- 3. The Holy Spirit and a Sense for the Faith -- Two. The Norm: Sensus Fidelium, Tradition, and Scripture -- 4. Receiving Jesus Christ in the Spirit -- 5. Authority and the Canon of Scripture -- 6. The Inspiration of Scripture -- Three . The Task: Sensus Fidelium, Theology, and Magisterium -- 7. The Threefold Teaching Office of the Church -- 8. Sensus Fidei and the Individual Believer -- 9. Sensus Fidelium and Teaching the Faith of the Church -- Epilogue: Ongoing Conversion of the Ecclesial Imagination -- Bibliography -- Index.